Wooly boys - Burzynski, Leszek; Fonda, Peter, 1939-; Kristofferson, Kris; Carradine, Keith, 1949- (Santa Monica, CA : Lions Gate Home Entertainment, 2005)
A woman convinces her estranged and ill father, Stoney, to come to the city for care and become reacquainted with his grandson. When Stoney's partner back at the sheep farm discovers where he is hospitalized, a grand escape plan is hatched.
Peter Fonda, Kris Kristofferson, Keith Carradine, Robin Dearden, Joseph Mazzello.
MPAA rating: PG.
DVD, Dolby digital 2.0 surround.
In English with optional Spanish subtitles.
Keywords: Grandparent and child -- Drama; Conflict of generations -- Drama; Feature films; Comedy films